Fungal and Bacterial Endophytes as Microbial Control Agents for Plant-Parasitic Nematodes - Kumar, K. Kiran (Int J Environ Res Public Health, 2021)
Endophytes are symbiotic microorganisms that colonize plant tissues and benefit plants in multiple ways including induced systemic resistance to biotic and abiotic stresses. Endophytes can be sustainable alternatives to chemical nematicides and enhance plant health in a variety of cropping and natural environments. Several in vitro and in vivo studies demonstrated the potential of multiple species of Fusarium and Bacillus against plant-parasitic nematodes in horticultural, agricultural, and fodder crops and in forestry. While there were efforts to commercialize some of the endophytes as bionematicides, a lack of good formulations with consistent field efficacy has been a major hurdle in commercializing endophytes for nematode control. Identification of efficacious and environmentally resilient strains, a thorough understanding of their modes of action, interactions with various biotic and abiotic factors, and developing strategies that improve their effectiveness are critical areas to advance the commercialization of bionematicides based on fungal and bacterial endophytes.